2018
DOI: 10.1016/j.ygeno.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of the transcription factor GLIS3 identifies its dual function in beta cells and neurons

Abstract: The GLIS family zinc finger 3 isoform (GLIS3) is a risk gene for Type 1 and Type 2 diabetes, glaucoma and Alzheimer's disease endophenotype. We identified GLIS3 binding sites in insulin secreting cells (INS1) (FDR q<0.05; enrichment range 1.40-9.11 fold) sharing the motif wrGTTCCCArTAGs, which were enriched in genes involved in neuronal function and autophagy and in risk genes for metabolic and neuro-behavioural diseases. We confirmed experimentally Glis3-mediated regulation of the expression of genes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…Improved glucose tolerance and increased circulating bile acids in GK rats following intestinal P. copri enrichment concur with its beneficial metabolic role. We hypothesise that naturally increased intestinal P. copri in the GK rat contributes to the complex aetiology of diabetes in this strain by counteracting the adverse effects of permanent hyperglycaemia, along with sequence variants in genes that stimulate insulin secretion [12] and downregulated expression of genes involved in heart failure [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved glucose tolerance and increased circulating bile acids in GK rats following intestinal P. copri enrichment concur with its beneficial metabolic role. We hypothesise that naturally increased intestinal P. copri in the GK rat contributes to the complex aetiology of diabetes in this strain by counteracting the adverse effects of permanent hyperglycaemia, along with sequence variants in genes that stimulate insulin secretion [12] and downregulated expression of genes involved in heart failure [42].…”
Section: Discussionmentioning
confidence: 99%
“…The Goto-Kakizaki (GK) rat is an inbred model of spontaneous diabetes obtained by selective enrichment of naturally occurring genetic polymorphisms [10] resulting in multifaceted pathological features relevant to type 2 diabetes in the absence of obesity. Even though diabetescausing genes have been mapped to the GK genome (reviewed in [11]) [12], bariatric surgery improves glycaemic control in this strain [13][14][15] through unknown mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A role for GLIS3 in the nervous system is further supported by studies showing that GLIS3‐deficiency leads to the development of mild mental retardation and facial dysmorphism, and the association of single nucleotide polymorphisms (SNPs) in GLIS3 with an increased risk of Parkinson's and Alzheimer's disease . A recent study found a correlation between Glis3 variants and a significant reduction in dendritic complexity and spine density, important characteristics in several neurodegenerative diseases . Overexpression of GLIS3 was reported to be associated with ependymomas, tumors arising from the ependyma of the central nervous system .…”
Section: Introductionmentioning
confidence: 95%
“…Thus GLIS3 transcription factor is implicated to regulate MANF expression in beta cells. GWAS have identified GLIS3 as a known risk gene for T1D and T2D ( Calderari et al, 2018 ). Patients with mutations in this gene show neonatal diabetes, skeletal and other defects.…”
Section: Manf Expression Is Differently Regulated In Beta Cells Upon mentioning
confidence: 99%
“…Importantly, Glis3 -/- mice become severe diabetic neonatally due to reduced beta cell mass ( Watanabe et al, 2009 ). In a genome-wide chromatin immunoprecipitation sequencing screen aimed at searching for Glis3 binding sites in INS-1 cells, 199 putative genes were found to bind Glis3 ( Calderari et al, 2018 ). Interestingly, genes with Glis3 binding sites were enriched for GWAS loci associated with metabolic diseases and neuropathologies.…”
Section: Manf Expression Is Differently Regulated In Beta Cells Upon mentioning
confidence: 99%